1995
DOI: 10.1007/bfb0102150
|View full text |Cite
|
Sign up to set email alerts
|

Physical and chemical variations within the W3 star-forming region

Abstract: Abstract. Results are presented of the 345 GHz spectral survey toward three sources in the W 3 Giant Molecular Cloud: W 3 IRS4, W 3 IRS5 and W 3(H 2 O). Nearly 90% of the atmospheric window between 334 and 365 GHz has been scanned using the James Clerk Maxwell Telescope (JCMT 1 ) down to a noise level of ∼ 80 mK per resolution element. These observations are complemented by a large amount of data in the 230 GHz atmospheric window. From this data set physical conditions and beam-averaged column densities are de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 58 publications
(108 reference statements)
6
61
0
Order By: Relevance
“…Helmich et al (1994) also reported that the CH 3 OH abundance is remarkably low, even compared to typical dark clouds. From our SMA data, and the results from Wang et al (2012), we find that sulfur-bearing molecules such as SO, SO 2 and their isotopologues, strongly peak toward the submillimeter sources SMM1 and SMM2 (zone A) with extended emission toward SMM3, SMM4 and SMM5 (Fig.…”
Section: Distinct Molecular Zonesmentioning
confidence: 94%
See 1 more Smart Citation
“…Helmich et al (1994) also reported that the CH 3 OH abundance is remarkably low, even compared to typical dark clouds. From our SMA data, and the results from Wang et al (2012), we find that sulfur-bearing molecules such as SO, SO 2 and their isotopologues, strongly peak toward the submillimeter sources SMM1 and SMM2 (zone A) with extended emission toward SMM3, SMM4 and SMM5 (Fig.…”
Section: Distinct Molecular Zonesmentioning
confidence: 94%
“…A JCMT spectral line survey characterized W3 IRS5 as a remarkable massive star-forming region with rich spectral features from sulfur-bearing molecules (Helmich et al 1994;Helmich & van Dishoeck 1997). Helmich et al (1994) also reported that the CH 3 OH abundance is remarkably low, even compared to typical dark clouds.…”
Section: Distinct Molecular Zonesmentioning
confidence: 99%
“…Helmich et al (1994). The estimated error on the line fluxes is a factor of two, due to the uncertain contribution from high-velocity gas.…”
Section: Molecular Abundancesmentioning
confidence: 98%
“…NGC7538 IRS9 and NGC7538 IRS1 are located in Perseus, and NGC7538 IRS1 is known to house a bright hot core 19 and is situated in the middle of a cluster of continuum peaks and molecular outflows. W3 IRS5 is associated with at least five young stellar objects, two of which are massive [20][21][22][23][24] , and is known to present strong S-bearing molecular lines 25 . In summary all three sources are known to have complicated structures with many different potential origins of complex molecular emission.…”
Section: Observations and Source Characteristicsmentioning
confidence: 99%